Food science and technology bulletin functional foods. Volume 7 - Gibson, Glenn R. (IFIS, 2011)
This book delivers concise and relevant peer-reviewed minireviews of developments in selected areas of functional foods.
Keywords: Functional foods.; Food industry and trade.; elektronické knihy; electronic books